COMPARATIVE EVALUATION OF THE EFFECTS OF DEXMEDETOMIDINE-PROPOFOL AND FENTANYL-PROPOFOL ON VARIOUS PARAMETERS DURING I-GEL INSERTION - KC, Suja; R, Sethunath; Joseph, Elizabeth; Cheeran, Susan T (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Supraglottic airway devices (SGAD) have become inevitable for routine and difficult airway management and various induction agents are used for SGAD insertion. The present study compares the insertion conditions for I-gel, using Dexmedetomidine and Fentanyl with Propofol. Methods: Sixty patients were included in the study and randomly divided into two groups. Group D received 1 mcg/kg Dexmedetomidine and Group F received 1 mcg/kg Fentanyl. The mean arterial blood pressure (MAP) and heart rate (HR) were recorded at baseline and after 1’, 3’ 5’, and 10’ after insertion. Results: A significant decrease in HR was seen in Group D at 3’, 5’, and 10’ after insertion when compared to its respective time intervals in Group F. However, when MAP was observed, the 5’ after insertion showed a decrease in blood pressure within the groups but when MAP between groups were compared, there was no significant variation between Group F and Group D at their respective time intervals after insertion. HR was significantly reduced with Dexmedetomidine compared to that with Fentanyl. Conclusion: Co-induction of Propofol with Fentanyl or Dexmedetomidine 1 mcg/kg provides satisfactory hemodynamic stability and comparable insertion condition for I-Gel.